2015
DOI: 10.1007/s00262-015-1719-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the innate immune activity in murine tumor microenvironment by a combination of inducer molecules attached to microparticles

Abstract: Targeted cancer immunotherapy is challenging due to the cellular diversity and imposed immune tolerance in the tumor microenvironment (TME). A promising route to overcome those drawbacks may be by activating innate immune cells (IIC) in the TME, toward tumor destruction. Studies have shown the ability to "re-educate" pro-tumor-activated IIC toward antitumor responses. The current research aims to stimulate such activation using a combination of innate activators loaded onto microparticles (MP). Four inducers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…We next analyzed the mechanism by which RIPK1-mediated inflammation might promote HCC in Tak1 ΔHEP mice. CD45 is an important marker for infiltrating lymphocytes in the tumor microenvironment (48,49). We found that TAK1 deficiency in Tak1 ΔHEP mice caused the prominent increases in the liver recruitment of CD45 + cells, which was suppressed by RIPK1 D138N mutation (Fig.…”
Section: Hepatocytic Tak1 Deficiency Promotes Liver Infiltration Ofmentioning
confidence: 77%
“…We next analyzed the mechanism by which RIPK1-mediated inflammation might promote HCC in Tak1 ΔHEP mice. CD45 is an important marker for infiltrating lymphocytes in the tumor microenvironment (48,49). We found that TAK1 deficiency in Tak1 ΔHEP mice caused the prominent increases in the liver recruitment of CD45 + cells, which was suppressed by RIPK1 D138N mutation (Fig.…”
Section: Hepatocytic Tak1 Deficiency Promotes Liver Infiltration Ofmentioning
confidence: 77%
“…In many instances, tumor formation is driven by the activation, recruitment, and accumulation of immune cells in the tumor milieu (12,34). Thus we next examined nonexclusive conventional immune cell markers to further our understanding of the role of this microRNA in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%